2016
DOI: 10.1186/s12896-016-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel pyruvate kinase and its application in lactic acid production under oxygen deprivation in Corynebacterium glutamicum

Abstract: BackgroundPyruvate kinase (Pyk) catalyzes the generation of pyruvate and ATP in glycolysis and functions as a key switch in the regulation of carbon flux distribution. Both the substrates and products of Pyk are involved in the tricarboxylic acid cycle, anaplerosis and energy anabolism, which places Pyk at a primary metabolic intersection. Pyks are highly conserved in most bacteria and lower eukaryotes. Corynebacterium glutamicum is an industrial workhorse for the production of various amino acids and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Contrary to the suggested hypothesis, we have not observed an increased glucose uptake rate for strains harboring a less active PK, but for the A271T mutant (Table 3 ). Notably, a simple in-frame deletion of pyk did not result in significant differences in comparison to the wild type regarding growth or glucose consumption as reported by previous studies 42 , 43 . Comparing PK amino acid sequence of C. glutamicum to the published structure of E. coli 44 (sequence identity of 41%) revealed that the two residues T12 and A20 are located in close vicinity to the catalytic center.…”
Section: Discussionsupporting
confidence: 79%
“…Contrary to the suggested hypothesis, we have not observed an increased glucose uptake rate for strains harboring a less active PK, but for the A271T mutant (Table 3 ). Notably, a simple in-frame deletion of pyk did not result in significant differences in comparison to the wild type regarding growth or glucose consumption as reported by previous studies 42 , 43 . Comparing PK amino acid sequence of C. glutamicum to the published structure of E. coli 44 (sequence identity of 41%) revealed that the two residues T12 and A20 are located in close vicinity to the catalytic center.…”
Section: Discussionsupporting
confidence: 79%
“…The catalytic activity of Pyk2 was allosterically regulated by fructose 1,6‐bisphosphate activation and ATP inhibition. The mRNA level of pyk2 under oxygen deprivation was higher than that under aerobic conditions (Chai et al, ). However, the effect of its deletion on DAP production has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we deleted pyk2 (cg3218, NCgl2809) and pyk (cg2291, NCgl2008) in the MQN6 strain. The pyk2 gene codes for pyruvate kinase (Chai et al, ). The catalytic activity of Pyk2 was allosterically regulated by fructose 1,6‐bisphosphate activation and ATP inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recently Chai et al. [ 51 ] found NCgl2809 as another novel pyruvate kinase (Pyk2) in C. glutamicum. These authors grew an engineered C. glutamicum containing Pyk1 or Pyk2 on D-ribose conditions, being the LA production enhanced by overexpression of either Pyk1 or Pyk2, due to the increase of the activity of the Pyk enzyme.…”
Section: La Producing Microorganismsmentioning
confidence: 99%